2003
DOI: 10.1103/physrevb.68.024422
|View full text |Cite
|
Sign up to set email alerts
|

Dipolar localization of quantized spin-wave modes in thin rectangular magnetic elements

Abstract: Dipole-exchange spectrum of quantized spin wave modes of a tangentially magnetized rectangular thin-film magnetic element is calculated using the method of tensorial Green's functions. The strong inhomogeneity of the internal bias magnetic field along the magnetization direction leads to the localization of spin wave modes either at the edges ͑exchange localization͒ or at the center ͑dipolar localization͒ of the element. The mode intensity distributions along the other in-plane direction are determined by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
82
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(86 citation statements)
references
References 26 publications
3
82
1
Order By: Relevance
“…The effective width felt by the centre modes is on the one hand smaller than the real width of the waveguide, i.e. w * < w, but the "magnetic wall" boundary condition is on the other hand not applicable to the model system, 44 suggesting that the centre modes in this system with the narrow antenna are not equivalent in nature to those reported in previous research. 21,24,[31][32][33] The edge and centre modes are degenerate in energy, yet spatially confined to different channels and of distinct dispersion relations.…”
Section: Resultscontrasting
confidence: 39%
See 1 more Smart Citation
“…The effective width felt by the centre modes is on the one hand smaller than the real width of the waveguide, i.e. w * < w, but the "magnetic wall" boundary condition is on the other hand not applicable to the model system, 44 suggesting that the centre modes in this system with the narrow antenna are not equivalent in nature to those reported in previous research. 21,24,[31][32][33] The edge and centre modes are degenerate in energy, yet spatially confined to different channels and of distinct dispersion relations.…”
Section: Resultscontrasting
confidence: 39%
“…The positions of the nodes are determined by the effective width w * of the waveguide felt by the centre mode, which is further associated with the boundary condition of the waveguide. 43,44 In our micromagnetic simulations, no boundary conditions were artificially imposed a priori on the lateral surfaces. In the theoretical calculations, the value of w * could not be chosen arbitrarily, otherwise the agreement with the simulations would not be accomplished.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently demonstrated [14] that a spinpolarized current can excite motion of magnetization in metallic nanomagnets with precession cone angles over 30° -values far exceeding those achievable in typical FMR experiments performed on bulk and thin-film samples. There are two reasons why it is possible to have such large-amplitude current-driven motions of magnetization in nanomagnets: (i) suppression of Suhl instability processes [15,16] due to quantization of the magnon spectrum in the nanomagnet [17][18][19][20][21][22][23][24][25][26][27][28], and (ii) efficient amplification of spin waves by spin transfer torque that can act approximately as negative magnetic damping [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on magnetic excitations in various thinfilm elements have been reported, including wires, [3][4][5][6][7] rectangles, 4,[8][9][10] circular disks 2,[11][12][13][14][15][16][17][18][19] and squares [20][21][22][23][24] with closure domains, rings, 25 and several other elementary shapes. In all examples listed above, the samples studied were essentially two-dimensional ͑2D͒, i.e., thickness effects are not important as far as the profile of the dynamic mode is concerned.…”
Section: Introductionmentioning
confidence: 99%